Impact of entrepreneurial curriculum on entrepreneurial competencies among students: The mediating role of the campus learning environment in higher education - Iqbal, Javed; Asghar, Muhammad Zaheer; Asghar, Ali; Waqar, Yasira (Frontiers in Psychology, 2022)
Purpose: This study explored the direct and indirect influence of entrepreneurial curriculum on entrepreneurial competencies, using campus learning environment as a mediator. Methods: In this study, a survey questionnaire composed of 48 items was used to collect data on entrepreneurial curriculum, entrepreneurial competencies and campus learning environment from pre-service vocational teachers enrolled in six universities located in Hunan province, China. The entrepreneurial curriculum has four components such as curriculum content, curriculum material, teaching strategies and feedback and assessment. Partial least squares structural equation modeling was used through SmartPLS 3.3.3 to measure the effects. Results: The curriculum content has a direct, significant, and positive influence on entrepreneurial competencies. For indirect influence, all four dimensions of entrepreneurial curriculum influenced the campus learning environment, which, in turn, was positively associated with entrepreneurial competencies. The campus learning environment was therefore revealed to play a mediating role between entrepreneurial curriculum and entrepreneurial competencies. Conclusion: The study explored that effective entrepreneurial curriculum delivery and campus learning environment are helpful for developing entrepreneurial competencies among the pre-service vocational teachers. Universities should take initiatives to update entrepreneurial curriculum and create a conducive campus learning environment that brings positive change to develop entrepreneurial competencies among their students. Moreover, practical implications and future research directions are also discussed in this study.